Modeling amplified arbitrary filtered heterodyne microwave photonic links - Sánchez, Erica; Pérez-López, Daniel; Pérez-Galacho, Diego; Huy-Ho, Tan; Wessel, David; Capmany, José (My University, 2022)
We report an end-to-end analytic model for the computation of the figures of nerit (FOMs) of arbitrarily filtered and amplified heterodyne coherent microwave photonics (MWP) links. It is useful for evaluating the performance of complex systems where the final stage is employed for up/down-converting the radio frequency (RF) signal. We apply the model to a specific case of complex system representing the front-haul segment in a 5G link between the central office and the base station. The model can be however applied to a wider range of cases combining fiber and photonic chip elements and thus is expected to provide a useful and fast tool to analyze them in the design stage.
Keywords: Filtros ópticos; Amplificadores ópticos; Microwave photonics; Optical signals; Optical systems; Radio over fiber